2019
DOI: 10.1101/579631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase-specific manipulation of neural oscillatory activity by transcranial alternating current stimulation

Abstract: Oscillatory phase has been proposed as key parameter defining the spatiotemporal structure of neural activity. Phase alignment of oscillations by transcranial alternating current stimulation (tACS) may offer a unique opportunity to enhance our understanding of brain rhythms and to alter brain function. However, the precise mechanism and effectiveness of tACS are still critically debated. Here, we investigated the phase-specificity of tACS effects on visually evoked steady state responses (SSR) measured by elec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…Our findings are unlikely to be due to a general tACS effect on motor performance as the phase of tACS relative to the visual stimulus would not be expected to affect performance in such case. Further, electrophysiological evidence for the efficiency of tACS applied over the occipital cortex in phase-specific modulation of SSVEPs has recently been reported, although in the alpha frequency range (Fiene et al, 2019). More broadly, our findings support the literature suggesting sensory perception is modulated by the phase of oscillations in the sensory cortices (e.g.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings are unlikely to be due to a general tACS effect on motor performance as the phase of tACS relative to the visual stimulus would not be expected to affect performance in such case. Further, electrophysiological evidence for the efficiency of tACS applied over the occipital cortex in phase-specific modulation of SSVEPs has recently been reported, although in the alpha frequency range (Fiene et al, 2019). More broadly, our findings support the literature suggesting sensory perception is modulated by the phase of oscillations in the sensory cortices (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Our Study contributes to the recently developing literature on concurrent use of tACS and periodic visual stimulation as a promising research technique in neuroscience (Ruhnau et al, 2016: Chai et al, 2018 and the importance of phase synchrony between them (Fiene et al, 2019) and demonstrate a behavioural effect for the first time. This will be of interest to researchers using electrical brain stimulation and sensory stimulation techniques.…”
Section: Discussionmentioning
confidence: 62%
“…Individualizing brain stimulation protocols has therefore been proposed as a crucial step to advance the theoretical and practical application of this line of research (25)(26)(27). A recent study (59) reported that the phase relation between tACS and visual flicker modulates the magnitude of EEG responses to the flicker when tACS is turned off. Moreover, the individual "best" phase relation between tACS and flicker (leading to strongest EEG responses) was correlated with the individual phase relation between EEG and flicker.…”
Section: Predicting Tacs Outcomes From Eeg Dataimplications For Futurmentioning
confidence: 99%
“…tACS involves the application of rapidly alternating electrical currents to the scalp and is assumed to cause periodic shifts in membrane potential and an entrainment (i.e., temporal phase alignment), of neural activity to the externally applied current [128,129]. Although the direct assessment of neural tACS effects in humans is still complicated by electrical artifacts in concurrent neural recordings, findings on behavioral effects during stimulation and analyses of electrophysiological stimulation aftereffects provide good evidence for the efficacy of tACS to modulate oscillatory activity in a phase- and frequency-dependent manner [130,131,132]. Lasting power and connectivity changes at the stimulation frequency have been interpreted as spike-timing-dependent plasticity effects as a consequence of synchronized activity during stimulation [131,133].…”
Section: Therapeutic Potential Of Tes For Cognitive Fatiguementioning
confidence: 99%